Bioinformatic analysis of wheat defensin gene family and function verification of candidate genes - Dong, Ye; Wang, Youning; Tang, Mingshuang; Chen, Wang; Chai, Yi; Wang, Wenli (Frontiers in Plant Science, 2023)
Plant defensins are widely distributed in the leaves, fruits, roots, stems, seeds, and tubers. Research shows that defensin in plants play a significant role in physiological metabolism, growth and development. Plant defensins can kill and suppress a variety of pathogenic bacteria. In this study, we understand the phylogenetic relationships, protein characterization, chromosomal localization, promoter and gene structural features of the TaPDFs family through sequence alignment and conserved protein structural domain analysis. A total of 73 PDF gene members in wheat, 15 PDF genes in maize, and 11 PDF genes in rice were identified. A total of 35, 65, and 34 PDF gene members were identified in the genomes of Ae. tauschii, T. urartu, and T. dicoccoides, respectively. TaPDF4.9 and TaPDF2.15 were constructed into pART27 vector with YFP by homologous recombination for subcellular localization analysis.Subcellular localization results showed that TaPDF4.9 and TaPDF2.15 were basically located in the cell membrane and cytoplasm, and TaPDF4.9 was also located in the nucleus. TaPDF4.9 and TaPDF2.15 could inhibit the infection of Phytophthora infestans strain ' 88069 ' . The results suggest that TaPDFs may be able to improve disease resistance. The study of wheat defensins will be beneficial for improving wheat yield and provides a theoretical basis for research on resistance to wheat diseases.